Upper lip changes on smiling in the vertical dimensions - Azad, Shimonti; Paul, Kajal Chandra; Mafruhah, Kazi; Saber, Bayezid Maruf; Saima, Umme Habiba (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: An attractive smile is considered as a valuable asset. As esthetically acceptable smile can never be created by beautiful teeth only, to establish harmony among teeth, lips and gingival display, pre-treatment evaluation of upper lip changes on smiling in the vertical dimensions helps the Orthodontists to determine the parameters that constitute an esthetically acceptable smile or pretty smile. Appropriate knowledge of soft tissue function and aesthetic help orthodontists to obtain stable and aesthetically appealing treatment results. Methods: The study was conducted on Ninety-six (96) participants (48 men, 48 women; aged 20 to 35). For each subject, nine (9) measurements of upper lip position and maxillary incisor crown height at rest and in maximum smile were recorded from their photographs. The photographic records were analyzed with the software for Windows, Digimizer medicalc 4.2.2. The individual measurements were correlated with sex distribution. Results: Relaxed and smiling external upper lip length and resting internal upper lip length was shorter in the women than in the men. Resting vermilion height and the maxillary central incisor height was also lesser in females than in males. The mean maxillary central incisor display at rest was greater in the women than in the men. Conclusion: Data from this study clearly indicated sexual dimorphisms in upper lip length, maxillary central incisor display and labial vestibular insertion. J Bangladesh Coll Phys Surg 2026; 44: 17-25